“AKTIVASI” MAKNA-MAKNA TEKS DENGAN PENDEKATAN KONTEMPORER: Epistemologi Hermeneutika Subjektif-Fiqhiyyah El-Fadl - Khabibi Muhammad Luthfi (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2017)
Abstract: This paper aims to review the use of hermeneutics Khaled M. Abou El-Fadl in finding a potential meaning of the text Quran and the hadith in terms of epistemology. It departs from El-Fadl is one of the contemporary Muslim intellectuals who has criticized the authoritarianism of most Muslims to be removed because against God and just believe in the single meanings. Though the text made by God to contain the potential meanings can be harmonized and contextualize the demands of the times. In addition, hermeneutic departing from the study of Islamic law or fiqh, which is often confused with the Quranic text or as fiqh is the text itself. With a philosophical approach based on literature data and discourse analysis found that El-Fadl offers hermeneutics subjective-fiqhiyyah based on the interaction between the text and the interpretive community and